ESTIMATING THE RISK OF CARDIO VASCULAR DISEASES AMONG PAKISTANI DIABETICS USING UK PDS RISK ENGINE - Moazzam, Amena; Amer, Javeria; Rehan, Naghma (Journal of Ayub Medical College Abbottabad, 2015)
Background: The concept of risk estimation of Coronary Heart Disease (CHD) is helpful for clinician to identifying high risk populations for their effective treatment. Latest studies recommended only initiating cardio-protective treatment in diabetic patients based on personalized CHD risk estimates so as to reduce undue harm from overly aggressive risk factor modification. The United Kingdom Prospective Diabetes Study (UK PDS) Risk Engine is a widely used tool to assess the risk of Cardio Vascular diseases (CVD) in diabetics. The literature search so far did not reveal any study of risk assessment among Pakistani Diabetics. Methods: This descriptive study is based on the data of 470 type-2 diabetics seen in Department of Endocrinology and Metabolism, Services Institute of Medical Sciences, Lahore during 2011. The data of these 470 patients was analyzed through UKPDS Risk Engine. CHD risk was calculated. Results: The 10 years risk of CHD, fatal CHD, stroke and fatal stroke was 9.4%, 4.4%, 1.7% and 0.2% respectively. Conclusions: The present study show a lower risk of CVD occurring among Pakistani diabetics as compared to studies from western countries. Keywords: Cardiovascular, Risk Assessment, Diabetics, UK PDS, Risk Engine, Pakistan